Researching Management Accounting-in-Action: l nterpretive Anthropology as a Methodological Discretion - Rasyid, Eddy R (The International Journal of Accounting and Business Society, 1994)
This article is about an analysis of the interplay between management accounting and organisational cultures. lt is con cerned on methodological arguments advocating the use ofinterpretive philosophy in gaining knowledge of how accounting is practised -accounting-in-action. lt is then shown that Geertzis interpretive cultural thought suggests an alternative perspective for an attempt to understand how management accounting is implicated in its cultural context.